(untitled) (Research, Society and Development, 2020)
To analyze the predictors and factors associated with the patient safety culture in the hospital environment. Quantitative cross-sectional study, conducted with 263 professionals randomly selected and submitted to the application of the Safety Attitude Questionnaire Instrument. Descriptive statistical analysis, Pearson correlation, variance analysis and linear regression were performed. In this context, the construct that obtained the highest average was the Satisfaction at work, while the lowest was the Perception of the performance of unit and organization management under the professional’s eyes. When comparing the means of the constructs, there was statistical significance between the teamwork climate and the unit of action, as well as the same construct with professional performance; Perception and influence of stress on work performance and professional positions; Job satisfaction and gender. In linear regression, the construct that most impacted was that of Perception of the performance of unit and organization management under the professional’s eyes. It is concluded that the most relevant predictor factor was the perception of the performance of the unit and organization management under the professional’s eyes. Such results may serve as a basis for further studies that take into account the influence of culture on patient safety actions.